Constructing Indignation: Anger Dynamics in Protest Movements. (July 2014) - Jasper, James M.
In recent years sociological research on social movements has identified emotional dynamics in all the basic processes and phases of protest, and we are only beginning to understand their causal impacts. These include the solidarities of groups, motivations for action, the role of morality in political action, and the gendered division of labor in social movements. Anger turns out to be at the core of many of these causal mechanisms.